Internet Financial Reporting dan Faktor-Faktor yang Mempengaruhinya Pada Pemerintah Kota dan Kabupaten Di Indonesia - Ariefia Nosihana; Rizal Yaya (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
This research identifies factors affecting the publication of financial reports in the internet or known as internet financial reporting (IFR) after the issuance of Home Minister Instruction No. 188.52/1797/SJ year 2012 on Improving Transparency of Local Budget Management. One hundred and seventy five cities and regencies were selected as samples based on purposive sampling and analysed by using multiple regression. The result shows that political competition and size of local government asset has positive influence on the IFR. This indicates that Heads of local government whose political party is not majority and Heads of local government with greater asset size, had used IFR as media to show their performance to the public. This is consistence with stewardships theory that asymmetric information between local government (stewards) with the public (principals) can be reduced through accountability and transparency of financial management whereby the pressure and ability to do it appeared significantly in local governments with high political competition and with relatively greater asset. In this research, some other potential factors such as leverage, own-source revenue, type of local government (city or regency) and audit opinion are not proven to influence the IFR practices in the local governments.